2010
DOI: 10.1143/jpsj.79.074715
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Superconductivity and Spin Fluctuations by Electron Overdoping in LaFeAsO1-xFx

Abstract: Low-energy spin fluctuations are studied for the electron-doped Fe-based superconductor LaFeAs-O 1Àx F x by inelastic neutron scattering up to an energy transfer of ! ¼ 15 meV using polycrystalline samples. Superconducting samples (x ¼ 0:057, T c ¼ 25 K and x ¼ 0:082, T c ¼ 29 K) show a dynamical spin susceptibility 00 ð!Þ comparable to that of the parent samples. However, 00 ð!Þ almost vanishes in the x ¼ 0:158 sample, in which the superconductivity is highly suppressed. These results are compatible with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
35
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 30 publications
13
35
1
Order By: Relevance
“…12(a)]. Similar measurements on powder samples of LaFeAsO 1−x F x (Ishikado et al, 2009;Shamoto et al, 2010;Wakimoto et al, 2010) and molecular-intercalated FeSe (Taylor et al, 2013) also revealed resonance like spin excitations below T c . Figure 12(c) shows temperature de-TABLE II Comparison of the effective magnetic exchange couplings for parent compounds of copper-based and iron-based superconductors.…”
Section: B Neutron Spin Resonance and Its Relationship With Superconsupporting
confidence: 58%
“…12(a)]. Similar measurements on powder samples of LaFeAsO 1−x F x (Ishikado et al, 2009;Shamoto et al, 2010;Wakimoto et al, 2010) and molecular-intercalated FeSe (Taylor et al, 2013) also revealed resonance like spin excitations below T c . Figure 12(c) shows temperature de-TABLE II Comparison of the effective magnetic exchange couplings for parent compounds of copper-based and iron-based superconductors.…”
Section: B Neutron Spin Resonance and Its Relationship With Superconsupporting
confidence: 58%
“…This is consistent with the observation of spin fluctuations in the optimally electron-doped 1111 system LaFeAsO 1−x F x using inelastic neutron scattering. 20 In summary, we have successfully observed chargeexcitation features in the RIXS spectrum of an iron pnictide, PrFeAsO 1−y (y=0,0.3). Calculations based on a 16 band dp model best reproduce the momentum dependence of the experimental dd interband feature for U =2.4 eV and J=0.48 eV, which confirms that the 1111 pnictides are moderately correlated.…”
mentioning
confidence: 74%
“…The gap temperature dependences measured in [28,29] using point-contact Andreev spectroscopy (PCAR) are typical for a strong interband coupling. A number of inelastic neutron scattering probes [35][36][37][38] reported rather sharp magnetic resonance peak in favor of the s ± model [15,16]. Nonetheless, the experimentally observed magnetic resonance peak seems [13,14] not so pronounced as predicted for s ± , and the s ± system would be unstable in a presence of impurities [13,39].…”
Section: Introductionmentioning
confidence: 95%